Vitamin D status after a high dose of cholecalciferol in healthy and burn subjects. Issue 5 (August 2015) - Rousseau, Anne-Françoise; Damas, Pierre; Ledoux, Didier; Lukas, Pierre; Carlisi, Agnès; Le Goff, Caroline; Gadisseur, Romy; Cavalier, Etienne
Highlights: Levels of 25OH-D at hospital admission following burn were straightaway lower than our healthy subjects. Efficacy of 100, 000 IU cholecalciferol to raise 25OH-D levels (and free 25OH-D levels) was quite uncertain, lower or even zero, in burn patients when compared to healthy subjects. Higher cholecalciferol doses than general recommendations should probably be considered during acute burn care. Interest of free 25OH-D is still questionable. Abstract: Background: Burn patients are at risk of vitamin D (VD) deficiency and may benefit from its pleiotropic effects as soon as acute phase. Aim of this observational study was to assess effects of a cholecalciferol (VD3) bolus on VD status in adult burn patients (Group B, GB) after admission, compared to healthy subjects (Group H, GH). Methods: Both groups received an oral dose of 100, 000 IU VD3. Blood samples were collected before (D0) and 7 days (D7) after bolus to measure 250H-D, 1, 25(OH)2 -D, parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23). Albumin (ALB) and VD binding protein (DBP) were measured and used to calculate free 25OH-D level. Data were expressed as median (min–max) or proportions. Results: A total of 49 subjects were included: 29 in GH and 20 in GB. At D0, prevalence of VD deficiency was higher in GB: 25OH-D was 21.5 (10.1–46.3) ng/ml in GH vs 11 (1.8–31.4) ng/ml in GB. DBP and ALB were lower in GB. At D7, DBP was stable in both groups while ALB decreased in GB. 25OH-D increased by 66.6 (13.5–260.3)% in GH. In GB, changes in 25OH-D extended from −36.7% to 333.3% with a median increase of 33.1%. Similar changes were observed in each group for free 25OH-D. High FGF23 levels were observed in GB. Conclusions: This study highlighted the differences in VD status and in response to a high dose VD3 in burn patients when compared to healthy patients. Pitfalls in VD status assessment are numerous during acute burn care: 25OH-D measurement needs cautious interpretation and interest of free 25OH-D is still questionable. They should not prevent burn patients to receive VD supplements during acute care. Higher doses than general recommendations should probably be considered.